Lattice Boltzmann Simulation of Bubble Dynamics in a Confined Channel - Goudarzi Karim, Ramin; Seyyed Esmaeil Najafi (Mechanical Technology and Engineering Insights, 2025)
In this study, a numerical analysis of the buoyancy-driven rise of a single bubble within a confined channel has been carried out by using the Shan-Chen multi-component multiphase Lattice Boltzmann Method (LBM). After verifying the numerical model by comparing results with those predicted by the Laplace law and bubble deformation for a square bubble, a series of numerical simulations has been conducted to explore the effects of the Eötvös number (2-60) and wall effects on bubble dynamics. It has been observed that, with increasing Eötvös number, bubble deformation increases. The bubble shape changes from an elliptical form at a low Eötvös number to a disk-like form at a high Eötvös number. Moreover, at an Eötvös number greater than or equal to 40, shear-induced bubble breakup has been observed. Moreover, streamline analysis shows that, with increasing Eötvös number, the strength of the wake vortex and the level of turbulence both increase. This argument can be explained by the decrease in damping with increasing Eötvös number. For bubbles released close to the wall, an asymmetric shear stress has been observed. This results in an oscillatory trajectory. With an increase in the Eötvös number, the level of oscillation increases. For an Eötvös number between 40 and 60, the oscillatory trajectory results from breakup. It has also been observed that the Morton number (Mo), has a negligible effect on bubble dynamics.